Efficacy evaluation of neoadjuvant chemotherapy in patients with HER2-low expression breast cancer: A real-world retrospective study - Tang, Lingfeng; Li, Zhenghang; Jiang, Linshan; Shu, Xiujie; Xu, Yingkun; Liu, Shengchun (Frontiers in Oncology, 2022)
Background: To characterize the clinicopathological features and evaluate the neoadjuvant chemotherapy (NACT) efficacy of patients with human epidermal growth factor receptor 2 (HER2)-low breast cancer. Methods: A total of 905 breast cancer patients who received 4 cycles of thrice-weekly standard NACT in the First Affiliated Hospital of Chongqing Medical University were retrospectively enrolled, including 685 cases with HER2-low expression and 220 cases with HER2-negative expression. Clinicopathological features were compared between patients with HER2-negative and HER2-low expression. Univariate and multivariate logistic regression analyses were used to find the independent factors of achieving a pathological complete response (pCR) after NACT. Results: There were significant differences in stage_N (P = 0.014), histological grade (P = 0.001), estrogen receptor (ER) status (P < 0.001), progesterone receptor (PgR) status (P < 0.001), NACT regimens (P = 0.032) and NACT efficacy (P = 0.037) between patients with HER2-negative and HER2-low expression breast cancer. In subgroup analysis, histological grade (P = 0.032), ER (P = 0.002), Ki-67 (P < 0.001) and HER2 status (P = 0.025) were independent predictors of achieving a pCR in ER-positive breast cancer. And the nomogram for pCR in ER-positive breast cancer showed great discriminatory ability with an AUC of 0.795. The calibration curve also showed that the predictive ability of the nomogram was a good fit to actual observations. Then, in the analysis of ER-negative breast cancer, only stage_N (P = 0.001) and Ki-67 (P = 0.018) were independent influencing factors of achieving a pCR in ER-negative breast cancer. Conclusion: HER2-low breast cancer was a different disease from HER2-negative breast cancer in clinicopathological features. Moreover, the NACT efficacy of HER2-low breast cancer patients was poorer.